Exploratory Study on Th1 Epitope-Induced Protective Immunity against Coxiella burnetii Infection - Xiong, Xiaolu; Qi, Yong; Jiao, Jun; Gong, Wenping; Duan, Changsong; Wen, Bohai (PLOS ONE, 2014)
Coxiella burnetii is a Gram-negative bacterium that causes Q fever in humans. In the present study, 131 candidate peptides were selected from the major immunodominant proteins (MIPs) of C. burnetii due to their high-affinity binding capacity for the MHC class II molecule H2 I-Ab based on bioinformatic analyses. Twenty-two of the candidate peptides with distinct MIP epitopes were well recognized by the IFN-γ recall responses of CD4+ T cells from mice immunized with parental proteins in an ELISPOT assay. In addition, 7 of the 22 peptides could efficiently induce CD4+ T cells from mice immunized with C. burnetii to rapidly proliferate and significantly increase IFN-γ production. Significantly higher levels of IL-2, IL-12p70, IFN-γ, and TNF-α were also detected in serum from mice immunized with a pool of the 7 peptides. Immunization with the pool of 7 peptides, but not the individual peptides, conferred a significant protection against C. burnetii infection in mice, suggesting that these Th1 peptides could work together to efficiently activate CD4+ T cells to produce the Th1-type immune response against C. burnetii infection. These observations could contribute to the rational design of molecular vaccines for Q fever.